Analysis of risk factors for acute attacks complicated by respiratory failure in children with asthma - Han, Peng; Jiao, Anxia; Yin, Ju; Zou, Huimin; Liu, Yuliang; Li, Zheng; Wang, Quan; Wu, Jie; Shen, Kunling (Frontiers in Pediatrics, 2024)
Objective: To describe the proportion and clinical characteristics of hospitalized children with acute asthma attacks complicated by respiratory failure and to analyze the risk factors. Methods: This retrospective study analyzed hospital admissions of children and adolescents with acute asthma attacks between January 2016 and December 2021. Inclusion criteria were used to identify eligible cases, and demographic information and disease characteristics were collected. Patients were categorized into respiratory failure group and the other group based on the result of artery blood gas analysis. Multivariate logistic regression was utilized to investigate the risk factors associated with respiratory failure resulting from acute asthma attacks. The data were analyzed using SPSS 22.0, and significance was considered at P<0.05. Results: Our research involved 225 participants, with 18.7% diagnosed with respiratory failure. The respiratory failure group was found to be younger and have higher percentage of male, while birth weight, nationality, and type of residence did not differ between the two groups. In the respiratory failure group, a significant difference was observed in emergency hospitalization, ICU treatment, severe to critical attack, dyspnea and allergy history. The two groups did not differ in admission season, first asthma diagnosis, respiratory infection and comorbidity. The respiratory failure group exhibited a higher proportion of atopy-only asthma and a lower proportion of T2-high asthma. The eosinophil count, and eosinophil percentage were lower in the respiratory failure group, while neutrophil count was higher. Having a history of allergies (OR = 2.46, 95% CI: 1.08-5.59) and neutrophil count (OR = 1.10, 95% CI: 1.00-1.21) were the risk factors for respiratory failure in children with asthma. There also existed that the risk of respiratory failure increases with decreasing age of the children (OR = 0.85, 95% CI: 0.73-0.99). Conclusion: Notably, risk factors for respiratory failure in hospitalized asthma children include age, having a history of allergies, and neutrophil count. The identification of the above factors and the implementation of timely intervention can optimize the treatment of asthma in children.